Inferiority Feeling Serta Aktivitas Fisik Siswa Obesitas dan Implikasi Pelayanan Bimbingan dan Konseling - Iqbal Arrahman; Firman Firman; Netrawati Netrawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to find out how to accept Class IX students. The purpose of this study was to increase students' low self-acceptance compared to their classmates. This study used case study methods. which means that the actual conditions that are evident in a situation and the conditions for this study to collect data are by interviewing, In addition, the role of guidance and counseling teachers in handling problems of students with low self-acceptance is to spread AUM (Problem Revealing Tool) to find out the problems that students are experiencing as early as possible. Six of the students who have low self-acceptance have slowly shown the results of their blending in with their friends and starting to participate in activities held both at school and around the residence.